Frontispiece: Molecular Assemblies of Metal Complexes via Base‐Pairing of Nucleic Acids in the Crystalline State. Issue 30 (29th May 2017) - Nakaya, Manabu; Ohtani, Ryo; Sugimoto, Kunihisa; Nakamura, Masaaki; Lindoy, Leonard F.; Hayami, Shinya
Abstract : The assembly arrangement of nucleobase‐appended terpyridine cobalt(II) complexes, [Co(A‐C6‐terpy)2 ](BF4 )2 and [Co(T‐C6‐terpy)2 ](BF4 )2 is investigated. In addition a single crystal structure of heteroleptic terpyridine cobalt(II) complexes, [Co(A‐C6‐terpy)(T‐C6‐terpy)](BF4 )2 has been obtained successfully for the first time. The complex exhibited dimer ring structure through the base pairings. This result shows that use of base pairings is useful for construction of supramolecular structures. For more details, see the Full Paper by S. Hayami et al. onpage 7232 ff.